DIMENSI MORAL SPIRITUAL PUTUSAN HAKIM Mencari Akar Masalah Rendahnya Kualitas Putusan Hakim - Nurul Huda (LPPM Universitas Pekalongan, 2014)
Public opinion of the poor quality of the judge’s decision is caused by many factors, one of which is not integrated with the judge’s riling basis of spiritual values as stated in the first principle of Pancasila as the state is about the value of Almighty God. Even within each head judge’s decision is always listed irah-irah decision reads “for the sake of justice based on God” which if interpreted contained values are very deep spirituality, which should be the basis of any decision of the judge.